TECHNOGENIC SOCIETY AND TECHNOGENIC CIVILIZATION: SIGNS, EVOLUTION, RISKS, CONTROL STRATEGY - Онопрієнко, В. І.; Онопрієнко, М. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
An analysis of such concepts as “technological society” and “technological civilization” has been made. It is marked that a new strategy of society’s control over the irrepressible scientific and technical development in the developed countries (first of all in Germany) is becoming the so called «Technology Assessment» conception.